Financial Crises, Dollarization, and Lending of Last Resort in Open Economies - Bocola, Luigi; Lorenzoni, Guido (American Economic Review, 2020)
Foreign currency debt is considered a source of financial instability in emerging markets. We propose a theory in which liability dollarization arises from an insurance motive of domestic savers. Since financial crises are associated to depreciations, savers ask for a risk premium when saving in local currency. This force makes domestic currency debt expensive, and incentivizes borrowers to issue foreign currency debt. Providing ex post support to borrowers can alleviate the effect of the crisis on savers’ income, lowering their demand for insurance, and, surprisingly, it can reduce ex ante incentives to borrow in foreign currency. (JEL E21, E42, E44, F34, G01)